Trends and characteristics of triplet births in a tertiary maternity hospital in China: A retrospective study over two decades - Yanzhen Zhou; Jinxiu Lin; Zhaozhen Liu; Sheng Lin (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Background: As triplet pregnancies were usually associated with poorer pregnancy outcomes and fetal reduction was coupled with procedure-related complications, many women with triplet pregnancies often opted for expectant management. This retrospective study reported the pregnancy outcomes of women with triplet pregnancies who did not receive artificial fetal reduction over a two-decade period (2002-2021). Methods: Maternal and pregnancy data and perinatal outcomes, including 111 triplets, were obtained from women with triplet pregnancies who received expectant management at Fujian Maternity and Child Health Hospital, including 111 triplets. The patient cohort was divided into two subgroups(Period I, 2002-2011 vs. Period II, 2012-2021). Results: Compared with those in the Period I group, participants in the Period II group reported a better educational background (28.8 vs. 13.8 %, p = 0.024), and occupation status (40.4 vs. 20.6 %, p = 0.012) and a greater percentage of primiparas (57.7 vs. 5.1 %, p < 0.005). However, compared with those in the Period II group, the period I group displayed significantly older gestation age at delivery(p = 0.001), heavier mean birth weight(1583.63 ± 62.14 vs.1830.51 ± 41.95 kg), higher rate of babies taken home(91.6 vs. 84.2 %,p = 0.049), and lower NICU admission rate(47.0 vs. 77.5 %, p < 0.005). Conclusions: Due attention to triplet pregnancies might lower the rate of maternity complications, and antenatal medicines to prevent prematurity could not prolong birth week. Developed neonatal treatment and nursing are adapted to stratified management based on chorionicity. With advancements in maternal healthcare and neonatal treatment, and nursing, expectant management could be a considerable option. Maternal factors such as parity and maternal education status might be correlated with gestational age.